(untitled) (UNWE Yearbook, 2015)
Today security is defined much more broadly than in the late 20th century and it has both military and non-military (humanitarian) aspects. The world is facing new and increasingly frequent challenges that can disrupt the balance. Emerging crisis (humanitarian, food, environmental) could be easily transferred to entire regions of the planet. Addressing these new challenges requires new research, new innovative approaches to decision and considering the economic aspects of security.Recent decades are characterized by intensive technological and product development. This conclusion is fully valid for security and defense sector. There are well-established trends in innovation that affect the innovation process in the security and defense sector. The environment for innovation characterizes by turbulence, a high degree of complexity and uncertainty. The mobility of the environment is different for various industrial sectors. Generally the environment does not stimulate and impede the innovation process in the security and defense sector.The main thesis of the study is that between the economy and security, there is an increasing complex interaction taking place through different channels and tools. Economic aspects of defense and security is not measured only through allocated to them public expenditure.There are several basic working hypotheses: 1) the interaction between the economy and security can be quantified and crises can be predicted; 2) innovation in defense and security can provide solutions in the economic system as a whole or to serve as a catalyst for economic development; 3) The environment for innovation is key to modern economic development.The goal of the study was to identify the characteristics of economic security in today’s economic and financial crisis and to identify the main features of the environment for innovation in security and defense. To achieve this purpose, the following tasks are performed: To identify the contemporary dimensions of security in the country and worldwide; to determine the relationship between the categories "security", "economy", "crisis" and "research"; to establish the characteristics of the environment for innovation in security and defense.